Recent advances on TD-SCDMA in China. - Bo Li (IEEE Communications magazine)
China has fully embraced the remarkable growth and unprecedented penetration of mobile services, and has become the world's largest mobile cellular market. TD-SCDMA was proposed by the China Wireless Technology Standard (CWTS) Group in 1998, approved as one of the 3G standards by ITU in May 2000, and joined 3GPP in March 2001. This has been a major effort by China to advance its mobile communication systems and facilitate its own technological development in this critical area. TD-SCDMA, a combination of TDD and synchronous CDMA, offers several unique advantages over its alternatives, WCDMA and cdma2000, such as flexible spectrum allocation, low-cost implementation, and easier migration from GSM systems. This article reviews the development, key technical features, and deployment of TD-SCDMA in China.